Analisis Pengaruh Sistem Pengupahan, Motivasi Kerja, Dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Ary Wijiningrum; E. Didik Subiyanto; Epsilandri Septyarini (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to determine the role of the Wage System, Work Motivation and Work Environment on Employee Job Satisfaction in the study on CV. Asa Putra Promosindo Purworejo. This research method uses descriptive quantitative and primary data using a questionnaire. The population in this study were all employees who worked at Cv. Asa Putra Promosindo Purworejo, totaling 130 employees. The sampling technique in this research is simple random sampling. Data was obtained by distributing a list of questionnaire questions to 99 respondents. The data source of this research is primary data. Test the quality of the data using the Validity Test, Reliability Test, and Classical Assumption Test. The data analysis technique in this study uses Multiple Linear Regression Analysis, t-Statistical Test, F-Statistical Test, and Coefficient of Determination (Adjust R2). The partial test results in this study indicate that the Wage System, Work Motivation and Work Environment Variables have a positive effect on Employee Job Satisfaction Cv. Asa Putra Promosindo. While the results simultaneously also show that the Wage System, Work Motivation and Work Environment together have a positive and significant effect on Employee Job Satisfaction Cv. Asa Putra Promosindo Purworejo. Keywords: Wage System, Work Motivation, Work Environment, Satisfaction Employee Work.